Evaluation of Morpho-physiological indices in autumn sugar beet (Beta vulgaris L.) cultivars under freezing stress at seedling stage - A. Nezami (Sugar Beet Seed Institute, 2013)
The physiological and morphological responses of seven sugar beet cultivars including three domestic cultivars (Jolge, PPB and SBSI1) and four exotic cultivars (Giada, Monotunno, Palma and Suprema) to freezing stress were studied in controlled environment in Agricultural College of Ferdowsi University of Mashhad in Iran. The experiment was performed as factorial with randomized complete block design arrangement in three replications. Plants were exposed to different freezing temperatures (0, - 2, -4, -6, -8, -10, -12, -14, -16 and -18 oC) at seedling stage. Percentage of electrolyte leakage, minimal fluorescence level in light-adapted leaves (Fs), maximal fluorescence level in light-adapted leaves (Fms), variable fluorescence (ΔF), efficiency of PSII photochemistry (ΔF/Fms), net photosynthesis rate, leaf number and area, radicle length and diameter, and survival percentage were measured. Monotunno cultivar showed higher survival (88%) and electrolyte leakage (26%) compared with other cultivars. The minimum (-16.9 oC) and the maximum (-15.2 oC) of lethal temperature 50% level according to survival percentage, and also the maximum (0.7%) and the minimum (0.59%) average of efficiency of PSII photochemistry, were observed in cultivars Monotunno and SBSI1, respectively. A negative and significant correlation (r=-0.65, P<0.001) was found between electrolyte leakage and survival percent-age, and also among recovered plants traits. Survival percentage showed significant and positive correlation with leaf number (r=0.88, p<0.001) and radicle length (r=0.87, p<0.001). A positive and significant correlation between survival percentage and ΔF/Fms ratio and also, a negative and significant correlation between ΔF/Fms with LT50su (r=-0.85, p<0.001) and lethal temperature 50% according to electrolyte leakage (LT50e1, r=-0.84, p<0.001), indicated that the cultivars which had a lower electrolyte leakage percentage and higher survival after recovering period, showed higher ΔF/Fms ratio. In tolerant cultivars, with decrease of electro-lyte leakage, the LT50su and LT50e1 indices were decreased significantly and a significant and positive correlation was observed be-tween these indices (r=0.75, p<0.05).